If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 3x + x = 1 Combine like terms: 3x + x = 4x 9 + 4x = 1 Solving 9 + 4x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 4x = 1 + -9 Combine like terms: 9 + -9 = 0 0 + 4x = 1 + -9 4x = 1 + -9 Combine like terms: 1 + -9 = -8 4x = -8 Divide each side by '4'. x = -2 Simplifying x = -2
| 8(7+5n)=256 | | -5x-2=-2x+10 | | 2(4x-2)=2(2x+2) | | -31-3x=-2(6x+2) | | 0.1b+0.6=0.5a | | x-(-88)=64 | | sin(x)+2=3 | | 5a-4=10a-1 | | 72.11*x^2+3490*x-61683.8=0 | | Y=3/5x-6 | | 7/2a=?/10ab^3 | | b/14=27/42 | | 4w+10=6w+13 | | 4/3b-11 | | 3x+0.5=1 | | 10x^2/35x | | 59-3x= | | A=9.87s/260 | | 168=6(1+4a) | | 81/9/3 | | (x^2+1)+(x+-8)=0 | | w^2+4w-1085=0 | | 24/6=X | | 11+r=4(2r+3)-1 | | (x^2+1)=(x-8) | | x+6-8x=3(5-2x)+x | | 1/10b=1 | | 0.1b-0.6=0.5a | | 0.3x-0.4x+6=2 | | a/12=33/36 | | x*.838=(x+50)*.6248 | | -33+4v=8-3(7-3v) |